Predictive nomogram for central lymph node metastasis in papillary thyroid microcarcinoma based on pathological and ultrasound features - Wang, Denghui; Hu, Ji; Deng, Chang; Yang, Zhixin; Zhu, Jiang; Su, Xinliang (Frontiers in Endocrinology, 2023)
Background: Central lymph node metastases(CLNM) in papillary thyroid microcarcinoma (PTMC) are common, but management through prophylactic central lymph node dissection (pCLND) remains controversial. In this study, the independent predictors of CLNM in PTMC were retrospectively studied based on ultrasound and pathological data, and we aim to establish the prediction model to predict CLNM in PTMC. Methods: This study included a total of 1506 patients who underwent thyroid surgery for PTMC in the First Affiliated Hospital of Chongqing Medical University from 2015 to 2018. Ultrasound and clinicopathological features were summarized and analyzed. Univariate and multivariate analyses were performed to determine the risk factors associated with CLNM. The prediction model is established and verified according to the multivariate analysis results. The Kaplan-Meier curve was used to evaluate the effect of CLNM on survival. Results: The CLNM rate was 44.5%(670/1506). Multivariate analysis showed that male, younger age, smaller diameter, ETE，microcalcification，without Hashimoto’s thyroiditis and multifocal were independent risk predictors of CLNM. Nomogram has good discriminative ability (C-index: 0.755 in validation group), and the calibration effect is good. In the DCA curve, the CLNM prediction model performed better net benefit given any high-risk thresholds. The median follow-up time was 30 months (12-59 months), 116 cases were lost, and the follow-up rate was 92.8%(1506/1622). Of the 1506 patients included, 12 (0.8%) experienced recurrence. Conclusion: The likelihood of CLNM can be objectively quantified before surgery by using this reliable and accurate nomogram that combines preoperative ultrasound with clinicopathological features. Clinicians can use this nomogram to assess central lymph node status in patients with PTMC, and consider prophylactic CND in patients with high scores.